Zimbabwe's Export Performance : The Impact of the Parallel Market and Governance Factors - Munoz, Sonia (IMF Working Papers; Working Paper ;, 2006)
This paper analyzes Zimbabwe's export performance in recent years and identifies the factors that could improve export performance, from both a quantitative and qualitative perspective. Improving export performance is critical to a turnaround in Zimbabwe's economic situation. The growth rate of total exports declined dramatically in the early 2000s, following a large real appreciation of the currency and the introduction of the fast-track land reform program. An important finding of the paper is that policies that reduce (eliminate) the parallel market premium and lower ethnic tensions would be key to promoting export growth.